Melatonin differentially regulates pathological and physiological cardiac hypertrophy: Crucial role of circadian nuclear receptor RORα signaling. Issue 2 (24th April 2019) - Xu, Longwei; Su, Yuanyuan; Zhao, Yichao; Sheng, Xincheng; Tong, Renyang; Ying, Xiaoying; Gao, Lingchen; Ji, Qingqi; Gao, Yu; Yan, Yang; Yuan, Ancai; Wu, Fujian; et al.
Abstract: Exercise‐induced physiological hypertrophy provides protection against cardiovascular disease, whereas disease‐induced pathological hypertrophy leads to heart failure. Emerging evidence suggests pleiotropic roles of melatonin in cardiac disease; however, the effects of melatonin on physiological vs pathological cardiac hypertrophy remain unknown. Using swimming‐induced physiological hypertrophy and pressure overload‐induced pathological hypertrophy models, we found that melatonin treatment significantly improved pathological hypertrophic responses accompanied by alleviated oxidative stress in myocardium but did not affect physiological cardiac hypertrophy and oxidative stress levels. As an important mediator of melatonin, the retinoid‐related orphan nuclear receptor‐α (RORα) was significantly decreased in human and murine pathological hypertrophic cardiomyocytes, but not in swimming‐induced physiological hypertrophic murine hearts. In vivo and in vitro loss‐of‐function experiments indicated that RORα deficiency significantly aggravated pathological cardiac hypertrophy, and notably weakened the anti‐hypertrophic effects of melatonin. Mechanistically, RORα mediated the cardioprotection of melatonin in pathological hypertrophy mainly by transactivation of manganese‐dependent superoxide dismutase (MnSOD) via binding to the RORα response element located in the promoter region of the MnSOD gene. Furthermore, MnSOD overexpression reversed the pro‐hypertrophic effects of RORα deficiency, while MnSOD silencing abolished the anti‐hypertrophic effects of RORα overexpression in pathological cardiac hypertrophy. Collectively, our findings provide the first evidence that melatonin exerts an anti‐hypertrophic effect on pathological but not physiological cardiac hypertrophy via alleviating oxidative stress through transactivation of the antioxidant enzyme MnSOD in a RORα‐dependent manner.